Implementation of Deep Learning Approach on Learning English at SMP Islam Tathmainul Quluub - Hidayat; Supriyani (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
This study analyzes the use of deep learning approaches in English teaching at SMP Islam Tathmainul Quluub, Sindang, Indramayu, focusing on meaningful, mindful, and joyful learning. Using a qualitative case study method, the research includes participatory observation, in-depth interviews, and documentation analysis. The findings indicate that educators successfully apply three main aspects of deep learning while adapting to the local context. Meaningful learning is achieved by connecting lessons to local issues, mindful learning through planned metacognitive strategies, and joyful learning by incorporating local cultures. Teachers face challenges with digital infrastructure when implementing hybrid learning models, and focus on strengthening their skills through ongoing professional development. Positive impacts include improved critical thinking, character development, social skills aligned with the '6C' concept, and increased student motivation. This application model demonstrates how schools in coastal areas can transform learning by integrating cognitive, social-emotional, and cultural elements.